Comparative Study of Use of Diathermy Vs Scalpel for Incision Making in Midline Laparotomy With Respect to Blood Loss - Junaid Khan Lodhi, Aasim Malik, Saba Tahir Bokhari, Muhammad Zubair (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Scalpels are used by surgeons for making incisions. Modern cautery units are used nowadays for making incisions. Aim: To evaluate and compare use of diathermy and scalpel for incision making in midline laparotomy with respect to incision time and blood loss. Method: This prospective randomized study was conducted at Surgical Unit1 Fatima Memorial Hospital from January 2017 to December 2018. Patients were categorized into diathermy and scalpel groups and evaluated for incision time and blood loss. Results: A total of 50 patients were included in the study with 25 (50%) patients in both diathermy and scalpel groups. For incision time, there was no difference found to be statistically significant in the diathermy and scalpel groups but pertaining to blood loss, less blood loss was calculated in diathermy group than in scalpel group. Conclusion: Diathermy is a primary choice for making incision to minimize blood loss in patients than scalpel. However, considering these options for incision time, none is superior to other.